Da escrita de "bastidores" à mensagem publicada: Revistas culturais e correspondência na trajetória editorial de Francisco José de Oliveira Vianna (Revista de História Regional, 2008)
This paper studies Francisco José de Oliveira Vianna's contributions to several magazines from different ideological-political groups. The research is based on letters received by Vianna, gathered on his personal private archive. Vianna was one of Brazilian First Republican Era most important thinker.